Comparison of conventional and reactive sintering techniques for Lead–Free BCZT ferroelectric ceramics. (July 2020) - Buatip, N.; Dhanunjaya, M.; Amonpattaratkit, P.; Pomyai, P.; Sonklin, T.; Reichmann, K.; Janphaung, P.; Pojprapai, S.
Abstract: Piezoelectric, dielectric and ferroelectric properties of a ceramic material greatly influenced by the synthesis technique and prepared condition. In this work, the efforts have been made to prepare barium calcium zirconium titanate (BCZT) ceramics and used to study the effectiveness of conventional sintering (CS) and reactive sintering (RS) methods. Specific composition of BCZT ceramic (Ba0.85 Ca0.15 Zr0.1 Ti0.9 O3 ) was achieved by suitable and verified sintering condition. Phase and structure of ceramics identified by using X-ray Diffraction (XRD). The result confirms the existence of pure perovskite structure and mixture phase of orthorhombic and tetragonal in both CS and RS sintering techniques. Surface morphology and grain size variations for different dwell times were studied using Scanning Electron Microscopy (SEM). In both CS and RS techniques, the optimal sintering condition (1540 °C and 2 h of dwell time) possess gives relatively high density, better electric and piezoelectric properties. RS technique emerged as an alternative for CS technique. The implementation of sintering conditions, driven effects and their role on the above-mentioned properties were discussed. Pre-edge fine structure (PEFS) and X-Ray absorption near edge spectroscopy (XANES) is employed to elucidate the variation and oxidation state of 4+ of Ti and Zr in BCZT ceramics. Highlights: Reactive sintering technique is a fabrication method without calcination process. Reactive sintering could be replaced a conventional solid state fabrication method. Reactive sintering is a cost & time effective fabrication to prepare the BCZT.